Narrative Didactics in Mathematics Education: Results from a University Geometry Course - Brandl Matthias; Vinerean Mirela (De Gruyter, 2023)
In a Swedish second semester course on Euclidean and non-Euclidean geometry in mathematics education at Karlstad University, a bridging teaching strategy comprising elements from Mathematics, Didactics, History, Literature, and Technology was applied by using the concept of Narrative Didactics and Digital Interactive Mathematical Maps developed by the Professorship for Didactics of Mathematics at the University of Passau, Germany. The complete assessment of the teaching strategy comprised both an evaluation of the technological and the narrative didactical scaffolding and was partly analysed previously concerning especially the technology acceptance aspect, while here we broaden and deepen the evaluation analysis of the application of narrative didactic elements. Regarding the latter, at the end of the course, students were asked to formulate a short historical-oriented narrative motivation for a school topic of own choice with the help of information provided by the timeline of the Mathematical Map. A representative example of these art-combining products is presented and evaluated according to elements of narrative didactics. Results indicate a fruitful, promising, and synergetic connection between different fields of Science, Technology, Engineering, the Arts, and Mathematics that can lead to a richer and more sustainable learning process in mathematics lessons both at university and school level.